2006
DOI: 10.1128/mcb.26.6.2019-2028.2006
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylase Inhibitors Induce VHL and Ubiquitin-Independent Proteasomal Degradation of Hypoxia-Inducible Factor 1α

Abstract: Adaptation to hypoxic microenvironment is critical for tumor survival and metastatic spread. Hypoxiainducible factor 1␣ (HIF-1␣) plays a key role in this adaptation by stimulating the production of proangiogenic factors and inducing enzymes necessary for anaerobic metabolism. Histone deacetylase inhibitors (HDACIs) produce a marked inhibition of HIF-1␣ expression and are currently in clinical trials partly based on their potent antiangiogenic effects. Although it has been postulated that HDACIs affect HIF-1␣ e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
243
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(252 citation statements)
references
References 57 publications
4
243
5
Order By: Relevance
“…Jeong et al, 2002;Qian et al, 2006), the acetylation hypothesis remains controversial since human ARD1 does not, at least directly, acetylate HIF1a (Arnesen et al, 2005;Bilton et al, 2005Bilton et al, , 2006Fisher et al, 2005;Murray-Rust et al, 2006). Instead, diverse other mechanisms have been proposed for the HDAC inhibitor-induced HIF-1 regulation; Kong et al (2006) showed that HDAC inhibitors induced the proteasomal degradation of HIF-1a by interacting with HSP70 and thereby disrupted the HSP70/HSP90 axis function. In the other hand, Fath et al (2006) reported that acetylation regulated HIF-1 function by targeting the HIF-1a/p300 complex, not by directly targeting HIF-1a.…”
Section: Discussionmentioning
confidence: 99%
“…Jeong et al, 2002;Qian et al, 2006), the acetylation hypothesis remains controversial since human ARD1 does not, at least directly, acetylate HIF1a (Arnesen et al, 2005;Bilton et al, 2005Bilton et al, , 2006Fisher et al, 2005;Murray-Rust et al, 2006). Instead, diverse other mechanisms have been proposed for the HDAC inhibitor-induced HIF-1 regulation; Kong et al (2006) showed that HDAC inhibitors induced the proteasomal degradation of HIF-1a by interacting with HSP70 and thereby disrupted the HSP70/HSP90 axis function. In the other hand, Fath et al (2006) reported that acetylation regulated HIF-1 function by targeting the HIF-1a/p300 complex, not by directly targeting HIF-1a.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the entire 19S subunit seems to exist in a dynamic equilibrium with the 20S catalytic subunit that possesses the ubiquitin-independent proteolytic functions and is clearly involved in the degradation of unubiquitinated proteins. Although most cellular proteins degraded in the proteasome are ubiquitinated, proteins such as ornithine decarboxylase, the Cdk inhibitor p21, Hif1a, members of the Rb family of tumor suppressors, p53 and p73 (Sdek et al, 2005;Kong et al, 2006) can be directed to the proteasome without prior ubiquitination. In many cases, if a protein can be delivered to the proteasome in a denatured or partially unfolded state, ubiquitination should not be required for its degradation.…”
Section: Discussionmentioning
confidence: 99%
“…The accepted physiological form of the proteasome is composed by the 20S core particle (the catalytic subunit) and two 19S regulatory caps that can dynamically associate in an assemble/disassembly cycle. A growing body of evidences is pointing to mechanisms of ubiquitin-independent proteasome degradation that appear to be widespread and physiologically important in higher eukaryotes (Sdek et al, 2005;Kong et al, 2006). In this context, the 20S proteasome subunit plays the major role being clearly involved in degradation of unubiquitinated proteins.…”
Section: Tbp-1 Regulates P14arf Oncosuppressor a Pollice Et Almentioning
confidence: 99%
“…Some of these effects may be indirect and attributed to the activity of HDAC6 as a regulator of HSP90 chaperone functions Murphy et al, 2005;Hurst et al, 2006;Kong et al, 2006).…”
Section: Nuclear Targets Of Hdac6mentioning
confidence: 99%